2012
DOI: 10.1038/ejhg.2012.65
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide scan with nearly 700 000 SNPs in two Sardinian sub-populations suggests some regions as candidate targets for positive selection

Abstract: This paper explores the genetic structure and signatures of natural selection in different sub-populations from the Island of Sardinia, exploiting information from nearly 700 000 autosomal SNPs genotyped with the Affymetrix Genome-Wide Human SNP 6.0 Array. The genetic structure of the Sardinian population and its position within the context of other Mediterranean and European human groups were investigated in depth by comparing our data with publicly available data sets. Principal components and admixture anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
18
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 54 publications
(61 reference statements)
4
18
1
Order By: Relevance
“…According to this approach, higher variability was observed in Northern Italian samples than in CentralSouthern and Sardinian ones, with haplotype variation being especially reduced in this latter group in accordance to the well-known high degree of isolation of Sardinians with respect to other Mediterranean populations (Table 1) (Cavalli-Sforza et al, 1994;Li et al, 2008;Piras et al, 2012). Although results from DAPC and AMOVA analyses (Supporting Information Fig.…”
Section: Discussionsupporting
confidence: 72%
“…According to this approach, higher variability was observed in Northern Italian samples than in CentralSouthern and Sardinian ones, with haplotype variation being especially reduced in this latter group in accordance to the well-known high degree of isolation of Sardinians with respect to other Mediterranean populations (Table 1) (Cavalli-Sforza et al, 1994;Li et al, 2008;Piras et al, 2012). Although results from DAPC and AMOVA analyses (Supporting Information Fig.…”
Section: Discussionsupporting
confidence: 72%
“…In general, Sardinia appears characterized by a large internal homogeneity [5], [7], like all isolated populations, even though other investigators suggested the presence of genetically different subpopulations in the island [6], [48]. Recently several genome-wide studies have been performed on Sardinian population taking advantage of the genetic homogeneity of the island using also large cohort of individuals [49], [50], [51], [52], [53].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, few autosomal genome-wide datasets have been generated until now to further disentangle this scenario and to explicitly test hypotheses related to occurrence of local adaptive events in diverse Italian subpopulations202122. In fact, genome-wide data suggested the existence of potential genetic barriers between Italians and other Europeans23 and further corroborated evidence for internal differentiation of the overall Italian population142224.…”
mentioning
confidence: 99%